Tsetse Flies and African Trypanosomiasis: Biology, Epidemiology, and Integrated Vector Control. - Mahesh Gaba*; Atul Khajuria1 (International Journal of Insects, 2026)
Tsetse flies (Glossina spp.) are hematophagous dipterans confined to sub-Saharan Africa and serve as cyclical vectors of human African trypanosomiasis (HAT) and African animal trypanosomiasis (AAT), with major implications for human health, livestock productivity, and rural development. An integrated understanding of tsetse biology, parasite transmission, climate, and land–use–driven distribution shifts, and the comparative performance of control tools—especially insecticides and sterile insect technique (SIT)—is essential for designing sustainable elimination strategies. HAT (sleeping sickness) is caused by Trypanosoma brucei gambiense in West and Central Africa and T. b. rhodesiense in East and Southern Africa, transmitted by infected tsetse flies. Historically, HAT has caused devastating epidemics, but coordinated vector control, improved diagnosis, and therapeutics have reduced reported cases to historically low levels, and elimination as a public health problem is now considered achievable. At the same time, AAT caused by T. congolense, T. vivax, and other trypanosomes remains a major constraint on cattle and other livestock, undermining food security and rural economies. From a microbiological perspective, HAT provides a paradigm of extracellular protozoan infection with sophisticated antigenic variation; from a public health perspective, it illustrates the challenges of vector- borne disease control under climate change, land use transformation, and constrained health systems.
Keywords: African animal trypanosomiasis; Glossina; Human African trypanosomiasis; KEY WORDS- Tsetse fly; Sterile insect technique; Vector control